2007
DOI: 10.1103/physrevc.75.054907
|View full text |Cite
|
Sign up to set email alerts
|

Strongly coupled plasma with electric and magnetic charges

Abstract: A number of theoretical and lattice results lead us to believe that Quark-Gluon Plasma not too far from Tc contains not only electrically charged quasiparticles -quarks and gluons -but magnetically charged ones -monopoles and dyons -as well. Although binary systems like charge-monopole and charge-dyon were considered in details before in both classical and quantum settings, it is the first study of coexisting electric and magnetic particles in many-body context. We perform Molecular Dynamics study of strongly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
325
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(353 citation statements)
references
References 44 publications
27
325
0
1
Order By: Relevance
“…This map is worked out in section 3, where the nature and role of the perturbative or non-perturbative objects driving the deconfinement transition is made quite explicit. We note that there have been earlier proposals and discussions of the role of various topological objects in the deconfinement transition, in the continuum and on the lattice, and that some bear resemblance to our discussion (see, for example, [14][15][16][17][18][19][20][21] and references therein). However, the study here stands out by being both analytic and under complete theoretical control.…”
Section: Deconfinement In Su(2) Qcd(adj)mentioning
confidence: 99%
See 1 more Smart Citation
“…This map is worked out in section 3, where the nature and role of the perturbative or non-perturbative objects driving the deconfinement transition is made quite explicit. We note that there have been earlier proposals and discussions of the role of various topological objects in the deconfinement transition, in the continuum and on the lattice, and that some bear resemblance to our discussion (see, for example, [14][15][16][17][18][19][20][21] and references therein). However, the study here stands out by being both analytic and under complete theoretical control.…”
Section: Deconfinement In Su(2) Qcd(adj)mentioning
confidence: 99%
“…The dimensional reduction of the T = 0 partition function (appropriate in the range of temperatures (3.3)) is equal to Z 0 Z 2d bion gas and is precisely the partition function of a XY model in a Villain approximation (see, e.g., [1]). 17 The "vortex-vortex" coupling K can be read off from the coefficient of the logarithm in the exponent in (3.5), which describes the interactions of vortices: 18…”
Section: Jhep04(2012)040mentioning
confidence: 99%
“…17 After some Kaluza-Klein frequency relabeling -responsible for the i = 1 shift in (3.19) -which is inessential since the W bosons and their Kaluza-Klein modes are integrated out (this gave rise to the particular combination of Ψ functions in (3.18)). 18 For θ = 0, notice that φ φ φ has no monodromy around electric charges. A Hamiltonian derivation of (3.22), based on further spatial compactification on T2, magnetic flux quantization, and the duality (3.9), is given in appendix A.…”
Section: The Fundamental Domain Of the Dual Photon For Different Choimentioning
confidence: 99%
“…3 Although phenomenological models relevant for the deconfinement transition with some degree of electric-magnetic duality have been proposed in [18].…”
Section: Summary Physical Picture and Outlookmentioning
confidence: 99%
“…Extensive studies over various many-body systems in the past have shown that the gas regime occurs with Γ << 1 while a liquid regime emerges universally at Γ ∼ 1 (see e.g. [29,30]). This therefore again hints at a strongly interacting glasma that may exhibit fluid-like behavior by virtue of high population.…”
Section: The Highly Overpopulated Glasmamentioning
confidence: 99%